INTRA‐RATER AND INTER‐RATER RELIABILITY OF THE FIVE IMAGE‐BASED CRITERIA OF THE FOOT POSTURE INDEX‐6 - Terada, Masafumi (Sports Physical Therapy Section, 2014)
PURPOSE/BACKGROUND: The Foot Posture Index‐6 (FPI‐6) is considered a simple quantification tool to assess static foot alignment. Palpation of the foot is required for assessment of one of the six criteria that comprise the FPI‐6; the remaining five criteria may be evaluated using still‐frame photographs. Using only the image‐based criteria may allow multiple clinicians to evaluate large groups of patients quickly. Reliability using only these five image‐based criteria has not been established. The purposes of the current study were to establish the inter‐ and intra‐rater reliability using five image‐based criteria from the Foot Posture Index‐6 (FPI‐6) as well as to examine the agreement between the raters in identifying foot type using the composite five FPI scores. METHODS: Forty participants (23 females, 17 males; 23.67 ± 8.49 years; 64.59 ± 14.43 kg; 166.07 ± 11.79 cm) volunteered for this study. An investigator took three photos with a digital camera of the medial longitudinal arch, posterior ankle, and of the talonavicular joint approximately 45° from the posterior calcaneus for both right and left feet. Two investigators assessed the five image‐based criteria of the FPI‐6 for both feet of 40 participants on three occasions separated by a day. Inter‐and intra‐rater reliability were assessed with Intraclass Correlation Coefficients (ICC(3,2)). The amount of agreement for classification of foot posture type between the two raters was assessed with Cohen's kappa coefficient. Significance was set a priori at P < 0.05. RESULTS: The inter‐rater reliability was poor to moderate for all three sessions (ICC(3,2) = 0.334‐0.634). For the foot posture classification, the amount of agreement between two raters was poor for left (κ= 0.12) and right (κ= 0.19) feet. The intra‐rater reliability was excellent for left (ICC(3,2)=0.956) and right feet (ICC(3,2)=0.959). CONCLUSIONS: Excellent intra‐rater and poor to moderate inter‐rater reliability was found using only the five image‐based criteria of the FPI‐6. However, the classification of foot posture did not improve the amount of agreement between raters. Therefore, caution is needed when interpreting FPI scores from five image‐based criteria. LEVELS OF EVIDENCE: 3b